A Precision Medicine Approach to the Treatment of Psychiatric Disorders (Global Journal of Medical Research, 2023)
Due to a lack of clarity about the pathophysiology of psychiatric disorders short and long-term treatment outcomes continue to be very inconsistent and the prescribing of multiple medications that can have unpredictable conflicting and sometimes paradoxical effects continues to be more the rule than the exception in modern psychiatric practice Dosing is also an issue as standard doses of psychotropic drugs are often too high thus causing some patients to incur unnecessary side effects which in turn can lead to poor compliance or even discontinuation of treatment Worse yet these negative outcomes can cause disappointed patients to dissuade other would-be patients from seeking treatment Recognizing these concerns and the fact that most persons with mental illness never seek treatment to begin with the need for greater precision and fewer side effects in the prescribing of psychotropic drugs cannot be overstated
Keywords: neuronal hyperexcitability; psychotropic drugs; antidepressants; antipsychotics; psychostimulants; anticonvulsants